2013
DOI: 10.1007/s10620-013-2859-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Benign Biliary Strictures Using Covered Self-Expandable Metal Stents (CSEMS)

Abstract: Benign biliary strictures can be effectively treated with CSEMS. Successful resolution of biliary strictures due to extrinsic disease is seen significantly less often than those due to intrinsic disease. Removal is successful in all patients with fully covered SEMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 34 publications
1
38
0
2
Order By: Relevance
“…Wagh et al [52] prospectively evaluated the efficacy of fully covered self-expandable metal stents as an alternative to plastic stenting in patients with biliary strictures, including those due to chronic pancreatitis. Similar findings were reported by Irani et al [53]. All of the failures were seen in patients with biliary strictures in the setting of chronic calcific pancreatitis.…”
Section: Endoscopic Management Of Chronic Pancreatitis Associated Bilsupporting
confidence: 89%
“…Wagh et al [52] prospectively evaluated the efficacy of fully covered self-expandable metal stents as an alternative to plastic stenting in patients with biliary strictures, including those due to chronic pancreatitis. Similar findings were reported by Irani et al [53]. All of the failures were seen in patients with biliary strictures in the setting of chronic calcific pancreatitis.…”
Section: Endoscopic Management Of Chronic Pancreatitis Associated Bilsupporting
confidence: 89%
“…Since that time, a large amount of retrospective clinical experience accrued using covered metal stents for a variety of benign biliary diseases in humans (2,3). These studies confirmed the animal studies showing that as long as the covering remained intact, the stents were removable.…”
mentioning
confidence: 69%
“…84 Irani et al performed a retrospective study of 145 patients using cSEMS for the decompression of benign biliary strictures. 85 Stricture resolution occurred in 66% of the patients with stent duration of 26 weeks. Extrinsic strictures were treated successfully in 49% of cases, with an 87% success rate in patients with intrinsic strictures.…”
Section: Plastic Vs Metal Stentsmentioning
confidence: 98%
“…All cSEMS were able to be removed. 85 Mahajan et al used 10 mm fcSEMS with fins in 44 patients with benign biliary strictures. Resolution of the strictures was confirmed in 83% of patients, with a median post-removal follow-up of 3.8 months.…”
Section: Plastic Vs Metal Stentsmentioning
confidence: 99%